Polar cap patches observed during the magnetic storm of November 2003: observations and modeling - Valladares, C. E. (2015)
We present multi-instrumented measurements and multi-technique analysis of polar cap patches observed early during the recovery phase of the major magnetic storm of 20 November 2003 to investigate the origin of the polar cap patches. During this event, the Qaanaaq imager observed elongated polar cap patches, some of which containing variable brightness; the Qaanaaq digisonde detected abrupt NmF2 fluctuations; the Sondrestrom incoherent scatter radar (ISR) measured patches placed close to but poleward of the auroral oval–polar cap boundary; and the DMSP-F13 satellite intersected topside density enhancements, corroborating the presence of the patches seen by the imager, the digisonde, and the Sondrestrom ISR. A 2-D cross-correlation analysis was applied to series of two consecutive red-line images, indicating that the magnitude and direction of the patch velocities were in good agreement with the SuperDARN convection patterns. We applied a back-tracing analysis to the patch locations and found that most of the patches seen between 20:41 and 21:29 UT were likely transiting the throat region near 19:41 UT. Inspection of the SuperDARN velocities at this time indicates spatial and temporal collocation of a gap region between patches and large (1.7 km s−1) line-of-sight velocities. The variable airglow brightness of the patches observed between 20:33 and 20:43 UT was investigated using the numerical Global Theoretical Ionospheric Model (GTIM) driven by the SuperDARN convection patterns and a variable upward/downward neutral wind. Our numerical results indicate that variations in the airglow intensity up to 265 R can be produced by a constant 70 m s−1 downward vertical wind.